2022
DOI: 10.20491/isarder.2022.1504
|View full text |Cite
|
Sign up to set email alerts
|

Duygusal Emek, İşgören Performansı ve Yaşam Tatmini Arasındaki İlişkilerin İncelenmesi: Otel İşgörenleri Üzerine Bir Araştırma(Examining the Relationships Between Emotional Labor, Employee Performance and Life Satisfaction: Research on Hotel Employees)

Abstract: Amaç–Bu araştırmanın amacı 5 yıldızlı otel işletmelerindeki işgörenlerin duygusal emek, performans ve yaşam tatminleri arasındaki ilişkileri incelemektir. Yöntem–Araştırmanın evrenini Antalya Belek’te faaliyet gösteren beş yıldızlı otel işletmelerinde çalışan işgörenler oluşturmaktadır. Araştırmada Duygusal Emek Ölçeği, İşgören Performansı Ölçeği ve Yaşam Tatmini ölçeği kullanılmıştır. Araştırma verileri kolayda örneklem yöntemi ile yüz yüze anket yapılarak toplanmıştır. 224 anket istatistiki an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A statistically positive and significant relationship was found between the deep behavior sub-dimension of the emotional labor dimension and life satisfaction. Ağbay et al (2022); In their study examining the effect of emotional labor on life satisfaction and employee performance, they found that employees exhibit false emotions, but this does not make any difference on life satisfaction (Ağbay et al, 2022(Ağbay et al, : 2335. The results obtained partially overlap with this study.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A statistically positive and significant relationship was found between the deep behavior sub-dimension of the emotional labor dimension and life satisfaction. Ağbay et al (2022); In their study examining the effect of emotional labor on life satisfaction and employee performance, they found that employees exhibit false emotions, but this does not make any difference on life satisfaction (Ağbay et al, 2022(Ağbay et al, : 2335. The results obtained partially overlap with this study.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…Life satisfaction is generally expressed as a cognitive evaluation of life as a whole (Ağbay et al, 2022(Ağbay et al, : 2327. According to a definition emphasizing the emotional dimension of the concept, life satisfaction is; While it is defined as the expression of the emotional state that emerges as a result of the person's evaluation of his or her general life; According to the definition emphasizing that this process is a perception, life satisfaction is the difference that a person perceives between his/her goals and what he/she realizes or achieves depending on the results arising from the interaction of the life conditions presented to him and the experiences he/she has experienced (Tutcu, 2018: 98).…”
Section: The Importance Of Life Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation